Implementasi Media Lagu dalam Meningkatkan Penguasaan Mufrodat Bahasa Arab Santri di Madrasah Diniyah - Nur Aizza Fillah; Isnol Khotimah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
Arabic language learning in madrasah diniyah still faces challenges in improving vocabulary mastery, particularly regarding students’ low motivation and memory retention of vocabulary. This study aimed to examine the implementation of songs as a medium in Arabic language learning and to analyze its improvement in students’ vocabulary mastery at Madrasah Diniyah Nurus Syamsi, Probolinggo. This study used a descriptive qualitative approach with research subjects consisting of 13 ula class students, one Arabic language teacher, and the head of the madrasah. Data were collected through participatory observation, semi-structured interviews, and documentation, and were then analyzed through the stages of data reduction, data display, and conclusion drawing using source and technique triangulation. The results showed that the use of songs as a medium was able to increase students’ enthusiasm, active involvement, memory retention, and pronunciation of vocabulary. Students found it easier to memorize vocabulary through rhythm and lyric repetition and showed higher learning motivation than in conventional methods. However, differences in students’ ages affected their level of understanding of vocabulary meanings. These findings confirm that songs are effective as a strategy for learning Arabic vocabulary in madrasah diniyah. The implications of this study indicate the importance of teacher creativity in selecting and adapting learning media to students’ characteristics so that the Arabic language learning process becomes more engaging, participatory, and meaningful.